Level of awareness on e-banking application among UiTM Jengka, Pahang lecturers / Nooraziah Md Diah, Nor Atiqa Md Nor and Siti Fatimah Salleh - Md Diah, Nooraziah; Md Nor, Nor Atiqa; Salleh, Siti Fatimah (2009)
This study is to find out the level of awareness on e-banking application among UiTM Pahang lecturers. Questionnaires have been distributed by using systematic sampling method to 30 respondents and 26 questionnaires were collected back and others 4 questionnaires did not get back. Data analysis was done by using SPSS version 16. The study showed that most of the respondents choose using on e-banking application. In this research report, we include the finding, from the finding, there were some recommendation for improving better e-banking application such as improved bank security, improved e-banking function, develop easier registration procedures, improved internet connection and improved consumer attitude. Besides that, there are two recommendations for future research such as type of research and sampling population. For the conclusion, this study, perhaps, can attract other researchers to explore much more detail towards this area of the study.